Prevalence and Predictors of Stroke Among Patients Presenting to the Emergency Department with Dizziness: A Retrospective Cohort Study - Alzahrani, Abdulelah; Alzahid, Abdullah; Almulihi, Qasem; Assiri, Mohammad; Subaih, Abdulrahman; Al Muhanna, Rayan; Khan, Yasir; Alabdullah, Manal; Alkallaf, Jood; Alhashim, Eyad; et al. (Archives of Academic Emergency Medicine, 2025)
Introduction: Dizziness is a frequent emergency department (ED) complaint, often benign but sometimes due to serious underlying etiologies, including cerebrovascular diseases. This study aimed to estimate stroke prevalence among ED dizzy patients and determine its predictors. Methods: This retrospective cohort study was performed at King Fahad Hospital of the University, reviewing all adult ED visits with documented dizziness from January–December 2023. Patients with incomplete records were excluded. Demographics, comorbidities, vital signs, and clinical features were studied and independent predictors of stroke among dizzy patients were identified using Logistic regression analysis. Results: A total of 1,660 records were reviewed and 950 adult patients with the mean age of 42.0 ± 16.2 (range 18-93) years were included. The prevalence of stroke was 0.74% (95% confidence interval (CI): 0.35 to 1.54). The prevalence was higher among males (1.60%) and patients aged 50-60 years (2.09%). Male sex (odds ratio (OR): 9.33, 95% CI: 1.12 to 77.8; p = 0.039), older age (OR: 1.05, 95% CI: 1.01 to 1.10; p = 0.017), smoking (OR: 21.8, 95% CI: 3.95 to 120; p < 0.001), diabetes (OR: 24.6, 95% CI: 2.94 to 205; p = 0.003), hypertension (OR: 5.25, 95% CI: 1.17 to 23.7; p = 0.031), hyperlipidaemia (OR:19.9, 95% CI: 4.37 to 91.3; p < 0.0001), tinnitus (OR:10.3, 95% CI: 1.17 to 90.9; p = 0.036), antiplatelet medications (OR: 8.80, 95% CI: 1.66 to 46.7; p = 0.011), and higher systolic blood pressure (OR: 1.04, 95% CI: 1.02 to 1.08; 0.001) were associated with an increased risk of stroke. In addition, presence of any focal neurologic deficit was significantly associated with the higher probability of stroke in dizzy patients. In the final logistic regression model, smoking (adjusted OR (aOR): 22.7, 95% CI: 2.96 to 174; p = 0.003), hyperlipidemia (aOR: 20.2, 95% CI: 3.45 to 117; p = 0.001), and systolic blood pressure (aOR: 1.06, 95% CI: 1.02 to 1.10; p = 0.001) remained significant independent predictors of stroke risk in dizzy patients who referred to the ED. Conclusion: Based on the finding of this series, the prevalence of stroke among dizzy patients was 0.74%. Older age, male sex, smoking, diabetes mellitus, hyperlipidaemia, tinnitus, antiplatelet medications, presence of focal neurologic deficit, and higher systolic blood pressure were among the associated factors of stroke in dizzy patients based on univariate analysis. Based on the final models, smoking, hyperlipidemia and increase systolic blood pressure were among the independent predictors of stroke in dizzy cases.